Murine Thigh Microdialysis to Evaluate the Pharmacokinetic/Pharmacodynamic Integration of Cefquinome Against Actinobacillus pleuropneumoniae - Zhang, Longfei; Zhou, Zichong; Gu, Xiaoyan; Huang, Sixiu; Shen, Xiangguang; Ding, Huanzhong (Frontiers in Veterinary Science, 2020)
This study aimed to explore the application of microdialysis in pharmacokinetic (PK)/pharmacodynamic (PD) integration of cefquinome against Actinobacillus pleuropneumoniae. After the A. pleuropneumoniae population reached 106 CFU/thigh, the mice received 0.04, 0.16, 0.63, 2.5, and 10 mg/kg cefquinome by subcutaneous injection. Plasma samples were collected by retro-orbital puncture for 4 h, and thigh dialysate was obtained by microdialysis at a flow rate of 1.5 μL/min for 6 h for the PK study. For the PD experiment, the infected mice were treated with a 4-fold-increase in the total cefquinome dose, ranging from 0.01 to 10 mg/kg/24 h, divided into one, two, three, four, and eight doses. The number of bacteria was determined and an inhibitory sigmoid maximum effect (Emax) model was used to analyse the relationships between PK/PD parameters and efficacy. The mean penetration of cefquinome from plasma to the thigh was 0.591. The PK data for PK/PD integration were obtained by extrapolation. The fittest PK/PD parameter for efficacy evaluation was %fT>MIC (the percentage of time that free drug concentrations exceed the MIC). The magnitudes of %fT>MIC to achieve net bacterial stasis, 1-log10 CFU reduction, 2-log10 CFU reduction, and 3-log10 CFU reduction were 19.56, 28.65, 41.59, and 67.07 % in plasma and 21.74, 36.11, 52.96, and 82.68% in murine thigh, respectively. Microdialysis was first applied to evaluate the PK/PD integration of cefquinome against A. pleuropneumoniae. These results would provide valuable references when we apply microdialysis to study the PK/PD integration model and use cefquinome to treat animal diseases caused by A. pleuropneumoniae.